Wood wood shelter: Development of a hiking shelter. Through a carpentry approach emphasising the expressive quality of exposed details - Eidenvall, Sara (My University, 2022)
One draws, the other builds, and the two never meet. Developments in the building industry have primarily shifted from craftsmanship driven to the organised construction industry. Conceivably the essential difference is that the creative idea and the practical work of the hand are now separated. In the craft tradition in Sweden, it was a long time when almost all men could build with timber. Today, we can state that we architects possess a much more limited knowledge of older building techniques and only exceptional specialised artisans master the traditional building crafts. The history of building technology is a possible way to connect the ability of the craft tradition with modern architecture and between architects and crafters. The project addressed this topic by having a close dialogue and collaboration with the craftspeople from an early stage as a leading method. At the same time, this master thesis seeks a practical strategy by working with a carpentry approach emphasising the expressive quality of exposed details implemented in a hiking shelter. Keywords: Timber, Log Structure, Architects & crafters, Research by design, Hiking shelter, Build 1:1 An old log house, Thun, Switzerland Time and money have also been constraints that have formed a framework for the design. In addition, different alternatives have been evaluated based on how much material and how long it takes to manufacture the profiles and assemble them. Accordingly, it also reflects the design result. The outcome has ended up using only one type of profile with an identical cross-section for the entire building, making the manufacturing process shorter and more affordable. In this process, a balance was essential in simplifying without compromising the crucial architectural concepts. This project aimed to illustrate how architects can work close to craftspeople from an early stage and, at the same time, highlight carpentry connections within architectural design. This project completes with a hiking shelter on a scale of 1:1 in Kroppefjäll nature reserve in Dalsland. Keywords: timber, log structure, architects and craftspeople, research by design, hiking shelter, build 1:1.
Keywords: Timber; Log structure; Architects & crafters; Research by design; Hiking shelter; Build 1:1